A practical tool to enhance the chances of success of digital agriculture interventions for sustainable development in Africa and India. Issue 6 (2nd November 2021) - Nitturkar, Hemant
ABSTRACT: Effective and sustainable tools, mechanisms and strategies are needed to significantly improve the prevailing agricultural productivity, farmer remuneration, and food availability globally to be able to meet the food, livelihood, and nutritional needs of the projected population in coming decades. Digital agriculture has the potential to efficiently bring together the benefits of the advances in agricultural research and the developments in information and communication technology space to help positively transform the entire spectrum of pre-farm to post-fork activities in the agriculture sector. Through interactions with over 338 stakeholders across India and Africa, supplemented with study of various digital agricultural interventions across the globe, the author observed that most digital agricultural interventions did not succeed, causing great loss of time and resources, which the world can ill afford. The world is falling behind on achieving the Sustainable Development Goals (SDGs). Drawing lessons from the failures and successes of the past digital agricultural interventions, the author has developed an innovative MS Excel tool called HeDAPSEE, to help estimate the success of a digital agricultural intervention before implementing it. This can help strengthen it in planning stages and enhance its chances of success.